Could Hepatitis B Reactivation be Overlooked in Patients with Resolved Hepatitis B Virus Infection and Receiving Immunosuppressive Treatment? - Acar, Şencan; Eminler, Ahmet Tarık (Turkish Journal of Gastroenterology, 2024)
Cite this article as: Acar Ş, Eminler AT. Could hepatitis B reactivation be overlooked in patients with resolved hepatitis B virus infection and receiving immunosuppressive treatment? Turk J Gastroenterol. 2024;35(4):350-351.